2020
DOI: 10.1038/s41598-020-67331-9
|View full text |Cite
|
Sign up to set email alerts
|

A new registration algorithm of electronic portal imaging devices images based on the automatic detection of bone edges during radiotherapy

Abstract: The precision and efficiency of the registration of megavolt-level electronic portal imaging devices (EPID) images with the naked eye in the orthogonal window are reduced. This study aims to develop a new registration algorithm with enhanced accuracy and efficiency. Ten setup errors with different translation and rotation were simulated with the phantom. For each error, one set of simulated computer tomography images and EPID images were acquired and registered with the traditional and the new method. The trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…To the best of our knowledge, this is the first study to examine 2D-3D registration algorithms during non-coplanar radiotherapy. In terms of the registration error for a 0°couch angle, the accuracy of our 2D-3D alignment algorithm is comparable to that of other 2D-3D alignment algorithms proposed in other studies [14,16]. For other couch angles, the maximum translation error along the z-axis (t z ) was less than 1.3 mm.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first study to examine 2D-3D registration algorithms during non-coplanar radiotherapy. In terms of the registration error for a 0°couch angle, the accuracy of our 2D-3D alignment algorithm is comparable to that of other 2D-3D alignment algorithms proposed in other studies [14,16]. For other couch angles, the maximum translation error along the z-axis (t z ) was less than 1.3 mm.…”
Section: Discussionsupporting
confidence: 69%
“…In radiation therapy, EPID is widely used as an online verification tool for patient positioning. The advantages of using portal imaging verification include but are not limited to the lower cost of imaging compared to CBCT imaging and the ability to readily combine the imaging dose of portal images with the treatment dose for dosimetry verification of radiotherapy treatments [14]. The lack of 3D patient anatomical information and the low contrast are evident registration limitations of portal images [4].…”
Section: Introductionmentioning
confidence: 99%
“…They found that multiscale enhancement yields better accuracy than top‐hat for lateral views; however, the improvement in performance was low for anterior–posterior (AP) fields. Chen et al 19 . introduced a new method for assessing the registration results of EPID images according to enhanced edge extraction without changing either the photon source or the detector.…”
Section: Related Workmentioning
confidence: 99%
“…They found that multiscale enhancement yields better accuracy than top-hat for lateral views; however, the improvement in performance was low for anteriorposterior (AP) fields. Chen et al 19 introduced a new method for assessing the registration results of EPID images according to enhanced edge extraction without changing either the photon source or the detector. Cheong claimed that the contrast-limited adaptive histogram equalization (CLAHE) 20 algorithm is the appropriate step for the quality enhancement on the MV EPID image in tumor tracking after assessing the individual contribution of deblurring, contrast improvement, and denoising.…”
Section: Related Workmentioning
confidence: 99%
“…ere will be no benefit for any side if a tiny miscalculation occurs; thus, higher requirements for the setup in radiotherapy are put forward. Scholars have studied the effects of body weight [1][2][3], respiration [4][5][6], body position fixation, molds [7][8][9], registration mode between planning images and CT images [10][11][12], and whether to wear a mask during the epidemic of COVID-19 [13][14][15] on the setup repeatability. To our best knowledge, few studies considered the weather conditions.…”
Section: Introductionmentioning
confidence: 99%